Effects of electromagnetic energy in irradiation of total suspended solids (TSS) and total desolved solids (TDS) and their effects on the turbidity in the municipal wastewater samples - Firas R. Al-Khalidy; Wisam J. Al-Hilo; M. Al-Ani (مجلة بغداد للعلوم)
Gamma radiation (most powerful radiation in penetrating materials) is used in the removal of the phenol from the wastewater samples taken from the effluent of sedimentation tank of AL-Rustamia wastewater treatment plant.